Organ Transplantation In Islamic Jurisprudence: A Comparative Ethical And Medical Study - Ali G Al Zuraib, Mohammd (Journal of Neonatal Surgery, 2025)
This study addresses the issue of human organ transplantation within the framework of Islamic jurisprudence, as one of the most pressing contemporary bioethical topics that intersect medicine, law, and theology. It aims to establish the legal and ethical foundation of organ donation from both living and deceased individuals, exploring emerging concepts such as brain death and bodily ownership. The paper compares Islamic legal positions with contemporary medical laws and ethical guidelines. The findings indi...